Implementation of LoRa on entrance and exit communication as determination of access to AI building, State Polytechnic of Malang - Hartadi, Berlian Mei; Kusumawardani, Mila; Suharto, Nugroho (Politeknik Negeri Malang, 2023)
The COVID-19 pandemic has changed many areas of life. One of the consequences is that the learning zone causes reduced mobility and limited face-to-face meetings. State Polytechnic of Malang in overcoming face-to-face learning, especially practical learning in the AI ??Building, of course, many students, not only have the need for practical lectures. The research that the author is doing here is a field research using a quantitative approach. This research was conducted at the AI Building of the State Polytechnic of Malang. In collecting the data needed the author uses observation techniques. Discussion used data analysis methods. The results of the research for the RSSI pattern with the transmit power set at 18dBm lora and the antenna frequency used at 433MHz obtained the RSSI value. At a distance of 2m to 8m there is a decrease in RSSI starting from -57dBm to -80dBm, continuing from a distance of 8m to 42m there is an ups and downs in RSSI. The throughput result is strongly influenced by the value of bytes and the time the throughput value when done twice scanning is smaller than four times scanning because the scanning processes have different times, this is in accordance with the calculation formula.